Global Trafficking Prevalence Data Distorts Efforts to Stop Patterns of Human Trafficking - Dottridge, Mike (Anti-Trafficking Review, 2017)
For everyone engaged in efforts to stop the exploitation and harm associated with human trafficking, it always sounds helpful to know how many people are being exploited in particular places and where they come from. Finding out should help us assess whether efforts to cut down these numbers are effective or not.